Center variation in screening for and management of metabolic syndrome in pediatric liver transplant recipients: A survey of SPLIT centers. (21st January 2019) - Hilk, Kelly; Zerofsky, Melissa; Rhee, Sue; Rosenthal, Philip; Perito, Emily R.
Abstract: Introduction: PTMS—a clustering of hypertension, dyslipidemia, glucose intolerance/diabetes, and obesity—is increasingly recognized as a contributor to long‐term morbidity after transplant. We sought to describe pediatric liver transplant center protocols and provider practices in screening for and managing these conditions. Methods: Cross‐sectional survey of pediatric liver transplant providers from centers that participate in Studies of Liver Transplantation (SPLIT). Results: Of 49 survey respondents from 39 centers, 64% were hepatologists or surgeons, 18% nurses/NPs/PAs, 12% coordinators, and 4% other. All providers felt that pediatric liver transplant recipients should be routinely screened for PTMS components. For each condition, at least 70% felt that the liver transplant team should be primarily responsible for routine screening. For each condition, at least 30% of providers reported that their center had no standardized protocol for screening. For diagnostic evaluation and initial management, >60% of providers reported that their center had no standardized protocol for glucose intolerance/diabetes, dyslipidemia, or obesity. Almost 40% had no standardized workup or initial management protocol for hypertension or chronic kidney disease. Of centers that did have screening or workup protocols, most were based on existing center practice, provider consensus, or informal review of published evidence. Screening tools, treatment steps, and thresholds for referral to another specialist varied widely. Conclusions: Transplant providers intend to screen for and initiate management of PTMS components in these children, but protocols and practices vary substantially. This highlights opportunities for multi‐center collaboration on protocols or interventions to improve screening and management.